Global longitudinal strain to determine optimal timing for surgery in primary mitral regurgitation: A systematic review. Issue 7 (30th March 2021) - Modaragamage Dona, Ann Christine; Afoke, Jonathan; Punjabi, Prakash P.; Kanaganayagam, Gajen S.
Abstract: Background: Primary mitral regurgitation (PMR) results in adverse remodeling changes and left ventricular (LV) dysfunction. Assessing LV function has prognostic value in predicting morbidity and mortality. Indications for surgery include parameters such as LV ejection fraction (LVEF) and systolic dimensions. Current guidelines are limited in identifying patients at optimal time for surgery. Impaired postoperative LVEF indicates poor prognostic outcomes and subsequent heart failure. Global longitudinal strain (GLS) via speckle tracking echocardiography (STE) presents as a promising parameter to detect subclinical dysfunction in asymptomatic patients. Methods: Following PRISMA guidelines, a literature search was conducted with Cochrane Library, PudMed, SCOPUS, and Web of Science. Key MeSH terms included "mitral regurgitation, " "mitral valve insufficiency, " "global longitudinal strain, " "deformation, " "LV‐GLS, " and "GLS." Inclusion criteria included (1) patients with severe PMR, (2) mixed population of symptomatic and asymptomatic patients, (3) standardized methods in assessing LV systolic function using 2D‐STE, (4) valve repair or replacement surgery, and (5) patient outcomes measured after surgery. Search returned 234 papers, 12 of which met the inclusion criteria and were subsequently reviewed. Results: Baseline GLS is an independent predictor of postoperative outcomes, ranging from −17.9 to −21.7% GLS. A significant negative correlation was observed between preoperative GLS and postoperative LVEF. Impaired baseline GLS was associated with higher mortality rates. Better long‐term survival rates were seen in patients who underwent early surgery. Conclusion: GLS shows sensitivity in predicting long‐term postoperative outcomes. Further analysis is required to determine preoperative GLS threshold to identify asymptomatic patients at the optimal time for mitral valve surgery.